Clinical efficacy of ambroxol combined with cefoperazone sodium and sulbactam sodium in the treatment of senile severe pneumonia - Lu Qiuying; Gao Yanfen; Shan Yan; Xu Yaping (Guoji laonian yixue zazhi)
[Objective] To investigate the clinical efficacy of ambroxol combined with cefoperazone sodium and sulbactam sodium in the treatment of elderly patients with severe pneumonia. [Methods] A total of 100 elderly patients with severe pneumonia admitted to our hospital from January 2022 to December 2023 were selected and divided into study group (n= 50, treated with ambroxol combined with cefoperazone sodium sulbactam sodium) and control group (n= 50, treated with cefoperazone sodium sulbactam sodium) according to random number table.After 2 weeks of treatment, the time to disappearance of clinical symptoms, pulmonary function (forced expiratory volume in 1 second, forced vital capacity, maximum mid-expiratory flow, peak expiratory flow rate), myocardial injury markers (N-terminal pro-brain natriuretic peptide, creatine kinase-MB isoenzyme, α-hydroxybutyrate dehydrogenase), inflammatory factors and immune parameters (C-reactive protein, procalcitonin, CD40 ligand, vascular cell adhesion molecule-1), acute physiology and chronic health status scores were compared between the two groups. [Results] After treatment, the disappearance time of clinical symptoms in study group was significantly shorter than that in control group(P<0.05); the lung function indicators increased, the levels of myocardial injury markers decreased, the inflammatory factors and immune indicators decreased, and the acute physiology and chronic health status scores decreased in both groups, and the study group was superior to the control group(P<0.05). [Conclusion] Ambroxol combined with cefoperazone sodium and sulbactam sodium in the treatment of elderly patients with severe pneumonia, compared with cefoperazone sodium and sulbactam sodium alone, can effectively shorten the time to disappearance of clinical symptoms, improve lung function and reduce myocardial injury markers and inflammatory factor levels, thereby promoting rapid recovery of patients.